(untitled) (Journal of the College of Basic Education, 2023)
Time is a great river, moving in a long stream, and if we stand on the shore of that river, we see a part of the water that has passed before us, and another that is still before us, and a third that has not come and has not yet run, but the same water that was present before us has become past, and another water has not yet passed, and so on. History.If time is a river, then history is a sea, and when I decided to write in the historical writing of the Arabs and to contribute to the study of Arab-Islamic history with what I took from the books and what the pen is rich in according to my own capabilities and the space of time, then I found in what I researched great glory, a long-standing heritage, great men, and an immortal history of the best nation that came out for people.The sources that I used in the research were few, not because of their inaccessibility or lack of knowledge of them, but rather because the topic of historical writing is a recent topic in the science of history, and if it is compared to other topics in this science. Very similar to the information they contain.